Evaluation of stress distribution characteristics on various bar designs of three-implant-supported mandibular overdentures - Emre Tokar; Serdar Polat; Bülent Uludağ (Gazi University, 2017)
Objective: Implant-supported-overdentures, instead of conventional complete dentures, are frequently recommended to rehabilitate patients having edentulous mandible. The aim of this study was to evaluate the stress distribution characteristics of mandibular implant-supported overdentures with four different bar attachment designs. Materials and Method: A photoelastic mandibular model with three implants (3.75 mm - 13 mm) placed at the interforaminal region was generated from a cast of an edentulous mandible. Four mandibular bar overdenture designs were fabricated: bar-clip, bar-galvano, bar-locator, and bar-ceka. Axial vertical loads (135 N) were applied to the central fossa of the right first molar area for each overdenture design. Stress concentrations were recorded photographically and analyzed visually. Results: The tested bar attachment designs revealed low and moderate stress levels. The lowest stress was observed with the bar-clip design, followed by bar-locator, bar-ceka, and bar-galvano designs. Conclusion: The loads were distributed to all of the implants. Studied designs experienced moderate stress levels around the loaded side implant. Bars with distally placed stud attachments and surface treatment with electroforming seems to increase stress levels around the implants.